Drosophila melanogaster mutant tan - Badaracco, Alejandra (2009)
Drosophila melanogaster gene tan was originally discovered in the early 20th century as a mutant strain lacking the dark pi gment pattern of wild-type (wt) f lies and, therefore, showing a light yellowish brown color (McEwen, 1918). Flies lack ing Tan function also exhibited abnormalities in vision (Benzer, 1967; Inoue et al. , 1988; True et al. , 2005), and tan males displayed an abnormal courtship behavior (Cook, 1980; Tomkins et al. , 1982). tan 1 ( t 1 ) and tan 3 ( t 3 ) alleles were found as spontaneous mutations, t 3 mutant being apparently lighter than t 1 (Brehme, 1941). tan is the structural gene for N- β -alanyldopamine hydrolase (NBAD-hydrolase or Tan protein), the enzyme that generates dopamine (DA) from NBAD (Wright, 1987; True et al. , 2005). Tan is expressed as a precursor protein of 43.7 kDa. Th is precursor is clea ved into two subunits of 29.9 and 13.8 kDa that apparently conform together a he terodimeric active protein (Wagner et al. , 2007). The enzyme that generates NBAD from DA, th e opposite reaction to the one catalyzed by Tan, is the NBAD-synthase or E bony protein (Wright, 1987; Pérez et al ., 1997), which is codified by the gene ebony . Since both Tan and Ebony ar e involved in cuticle tanni ng, carcinine re gulation, and NBAD metabolism in nervous tissue (Wright, 1987; Pérez et al. , 1997, 2004; Hovemann et al. , 1998; Borycz et al. , 2002; True et al. , 2005), it has been suggested that they function together in a system regulating the levels of dopamine during cuticle sclerotization a nd histamine in the visual metabolism (Borycz et al. , 2002; Pérez et al. , 2010). During the last few years, several publicati ons appeared regarding NBAD-synthase (Wappner et al ., 1996a, b; Pérez et al ., 1997, 2002, 2004, 2010; Hovemann et al. , 1998; Borycz et al. , 2002; Wittkopp et al., 2002; Schachter et al ., 2007), but very little is known about tan (True et al. , 2005; Wagner et al. , 2007). Thus, it was important to furthe r characterize the NBAD-hydrolase in D. melanogaster wt and in mutants t 1 and t 3.